Modified rare earth ferrite aerogel-based shielding-heat conduction-anticorrosion multifunctional composite material and preparation method thereof

By using modified rare earth ferrite aerogel-based composite materials in electromagnetic shielding materials to build conductive paths and design thermal conductivity, the problem that existing materials are difficult to have both strong electromagnetic shielding, thermal conductivity and corrosion protection, and multi-functional Integrated high-performance composite material.

CN119432079AActive Publication Date: 2025-02-14NANJING UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411783025.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-02-14
Estimated Expiration
2044-12-05

AI Technical Summary

Technical Problem

While achieving strong electromagnetic shielding effect, existing electromagnetic shielding materials are difficult to have excellent thermal conductivity and corrosion resistance. Especially in miniaturized and lightweight electronic equipment, high density and high cost metal fillers limit it. It is used, and the surface metal filler is easily corroded and affects long-term use.

Method used

Modified rare earth ferrite aerogel-based composite material with a mesh structure is used to build conductive paths through modified rare earth reinforced aerogels to achieve excellent shielding performance, and cast Co2 with excellent thermal conductivity through structural design Methsiloxane elastomer improves thermal conductivity and realizes the integration of shielding-thermal conductivity-anti-corrosion multifunctional integration.

Benefits of technology

It has achieved a composite material with strong electromagnetic shielding, excellent thermal conductivity and good corrosion resistance under low filling amount. It is suitable for communication equipment, vehicle-mounted radar and national defense fields, and has important application value and practical significance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119432079A_ABST
    Figure CN119432079A_ABST
Patent Text Reader

Abstract

The invention discloses a modified rare earth ferrite aerogel-based shielding-heat conduction-anticorrosion multifunctional composite material and a preparation method thereof.The preparation method comprises the steps that modified rare earth ferrite, pyrrole, ferric trichloride and an aramid fiber aqueous solution are mixed and stirred, and a modified rare earth ferrite enhanced aramid fiber solution is obtained; freeze-drying the modified rare earth ferrite enhanced aramid fiber solution to obtain modified rare earth ferrite enhanced aerogel; and pouring a heat-conducting filler / polydimethylsiloxane elastomer onto the modified rare earth ferrite reinforced aerogel, carrying out vacuum packaging, and curing to obtain the modified rare earth ferrite aerogel-based shielding-heat-conducting-corrosion-resistant multifunctional composite material with a net structure. The material prepared by the invention can realize the integration of multiple functions of shielding, heat conduction and corrosion prevention, has important application value in the fields of communication, vehicle-mounted radar and national defense, and has important practical significance in the application of electromagnetic shielding materials in the future.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electromagnetic shielding materials, and specifically relates to a modified rare earth ferrite aerogel-based shielding-heat-conducting-anti-corrosion multifunctional composite material with a mesh structure and a preparation method thereof. Background Art

[0002] While electronic and electrical equipment has brought great convenience to people's lives, it has also caused increasingly serious electromagnetic pollution. Electromagnetic waves will not only interfere with the normal use of other components and make electronic equipment unable to operate normally. It will also cause harm to human health. Studies have shown that when exposed to electromagnetic radiation, the risk of mild or acute diseases such as cancer, heart disease, and skin diseases increases. Therefore, the development of high-performance electromagnetic shielding materials has become a research hotspot. But at the same time, the reflected electromagnetic waves caused by electromagnetic shielding will cause electromagnetic energy to be converted into heat energy. The heat accumulated inside the instrument and composite materials will affect the normal operation and service life of the instrument. In addition, the electromagnetic shielding materials on the surface of the instrument are often affected by harsh environments, and improving the anti-corrosion performance plays a vital role in the long life of the composite materials. Therefore, the design of composite materials with strong electromagnetic shielding effects and excellent thermal conductivity and anti-corrosion properties has broad application prospects in the fields of communication equipment and consumer electronics.

[0003] Traditional electromagnetic shielding thermal conductive materials often add a large amount of metal fillers with both electrical and thermal conductivity to the material matrix. However, with the requirements of miniaturized and lightweight electronic devices, the high density and high cost of metal fillers are increasingly limiting their further application. In addition, the surface metal fillers are easily corroded, which is not conducive to long-term use. Composite materials that achieve strong electromagnetic shielding, high thermal conductivity and anti-corrosion effects at low filling amounts through structural design in the material have become a key issue that needs to be solved urgently. Summary of the invention

[0004] In view of the deficiencies in the prior art, the present invention provides a modified rare earth ferrite aerogel-based shielding-heat-conducting-anti-corrosion multifunctional composite material with a mesh structure and a preparation method thereof.

[0005] In order to achieve the above technical objectives, the present invention adopts the following technical solutions:

[0006] (I) The present invention provides a method for preparing a modified rare earth ferrite aerogel-based shielding-heat-conducting-anti-corrosion multifunctional composite material, comprising the following steps:

[0007] Step 1: Mixing and stirring the modified rare earth ferrite, pyrrole, ferric chloride and aramid fiber aqueous solution to obtain a modified rare earth ferrite reinforced aramid fiber solution;

[0008] Step 2: freezing the modified rare earth ferrite reinforced aramid fiber solution, and drying the frozen sample to obtain a modified rare earth ferrite reinforced aerogel;

[0009] Step 3: pour the thermal conductive filler / polydimethylsiloxane elastomer onto the modified rare earth ferrite reinforced aerogel, vacuum package it and then cure it to obtain a modified rare earth ferrite aerogel-based shielding-thermal conductive-anti-corrosion multifunctional composite material with a network structure.

[0010] Furthermore, in step one, the weight ratio of the modified rare earth ferrite, pyrrole, ferric chloride and aramid fiber aqueous solution is (4-8):(2-5):(2-5):(72-92), and more preferably (5-8):(4-5):(4-5):(72-92).

[0011] Furthermore, in step 1, the modified rare earth ferrite is neodymium-doped W-type barium ferrite, whose molecular formula is Ba 1-x Nd x Co2Fe 16 O 27 , x is 0.10, 0.15 or 0.20; the preparation method is: Ba 2+ 、Nd 3+ 、Co 2+ and Fe 3+ The salt is mixed with deionized water, citric acid is added and stirred to dissolve, and after the solution is adjusted to be neutral, the temperature is increased and stirred until a viscous gel is generated; the gel is further heated to remove excess water, and then the temperature is increased to 190-220° C. to obtain a precursor, and the precursor is ground; the ground precursor powder is calcined and ground to obtain neodymium-doped W-type barium ferrite.

[0012] Furthermore, the molar ratio of citric acid to metal ions is 1:1; the calcination process is: placing the ground precursor powder in a muffle furnace, pre-calcining at 450°C for 3 hours at a heating rate of 5°C / min, and then heating to 1300°C at a heating rate of 5°C / min and keeping warm for 3 hours.

[0013] Furthermore, in the step 1, the preparation method of the aramid fiber aqueous solution is: completely dissolving calcium chloride, p-phenylenediamine and terephthaloyl chloride in nitrogen methyl pyrrolidone, stirring at 150-400rpm for 3-6h to react; adding water to the solution after the reaction and stirring, stirring with a glass rod while adding, letting it stand after stirring and filtering, using a filter to wrap the viscous solution to obtain a synthetic aramid fiber aqueous solution; the addition ratio of calcium chloride, p-phenylenediamine, terephthaloyl chloride, nitrogen methyl pyrrolidone and water is 20g:3g:12g:70g:1000ml.

[0014] Furthermore, in step 2, the freezing temperature is -20°C and the drying temperature is 60-100°C.

[0015] Furthermore, in the step three, the curing method is: after the vacuum packaging is completed, it is placed in a forced air drying oven, and the temperature is set to 80-100° C. to obtain a cured modified rare earth ferrite aerogel-based shielding-heat-conducting-anti-corrosion multifunctional composite material.

[0016] Furthermore, in the step three, the preparation method of the thermally conductive filler / polydimethylsiloxane elastomer is: blending the thermally conductive filler with the component A of the polydimethylsiloxane elastomer, stirring once, then adding the component B of the polydimethylsiloxane elastomer, stirring the mixture a second time, and placing it in a vacuum oven for degassing to obtain the thermally conductive filler / polydimethylsiloxane elastomer.

[0017] Furthermore, the mass ratio of the thermal conductive filler, the component A of the polydimethylsiloxane elastomer and the component B of the polydimethylsiloxane elastomer is (20-30):(35-40):(35-40); the first stirring time is 20 minutes, and the second stirring time is 20 minutes.

[0018] Furthermore, the thermally conductive filler has a density of 2.3 g / cm 3 Boron nitride, 3.3g / cm 3 Aluminum nitride, 3.2g / cm 3 Silicon carbide and 4.0g / cm 3 At least one of aluminum oxides.

[0019] (ii) The present invention also provides a modified rare earth ferrite aerogel-based shielding-heat-conducting-anti-corrosion multifunctional composite material with a mesh structure, which is prepared by the preparation method described above.

[0020] Beneficial effects:

[0021] The present invention provides a modified rare earth ferrite aerogel-based shielding-heat conduction-anticorrosion multifunctional composite material with a mesh structure and a preparation method thereof. The conductive path is constructed by modifying the rare earth-enhanced aerogel to achieve excellent shielding effectiveness under corrosive conditions. Then, a polydimethylsiloxane elastomer with excellent thermal conductivity is cast through structural design to improve the thermal conductivity and achieve shielding-heat conduction-anticorrosion multifunctional integration. It has important application value in the fields of communications, vehicle-mounted radars and national defense, and has important practical significance in the application of electromagnetic shielding materials in the future. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a comparison diagram of electromagnetic shielding performance between the embodiment of the present invention and the comparative example sample;

[0023] Figure 2This is a comparison chart of the anti-corrosion performance of the examples of the present invention and the comparative examples;

[0024] Figure 3 This is a scanning electron microscope image of the sample of Example 1 of the present invention. DETAILED DESCRIPTION

[0025] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0026] The experimental methods used in the following examples are conventional methods unless otherwise specified, and the reagents, methods and equipment used are conventional reagents, methods and equipment in the art unless otherwise specified.

[0027] Example 1

[0028] This embodiment provides a modified rare earth ferrite aerogel-based shielding-heat-conducting-anti-corrosion multifunctional composite material, and its preparation method includes the following steps:

[0029] Step 1: Prepare a modified rare earth ferrite reinforced aramid fiber solution.

[0030] By weight, 20 parts of calcium chloride, 3 parts of p-phenylenediamine and 12 parts of terephthaloyl chloride are completely dissolved in 70 parts of nitrogen methyl pyrrolidone, the stirrer speed is adjusted to 300 rpm, and the reaction is carried out for 4 hours; 1000 ml of deionized water is added to the solution after the reaction, and a glass rod is used to stir while adding. The product is allowed to stand for a period of time to precipitate and then filtered. The viscous solution is wrapped with a filter to obtain a synthetic aramid fiber aqueous solution.

[0031] Neodymium-doped W-type barium ferrite was prepared by sol-gel method. The molecular formula of neodymium-doped W-type barium ferrite is Ba 1- x Nd x Co2Fe 16 O 27 , x is 0.10; the preparation method is: firstly according to the molar ratio of the molecular formula (Ba 2+ :Nd 3+ :Co 2+ :Fe 3+=1-x:x:2:16) Weigh several metal ion nitrates, dissolve in some deionized water, add monohydrated citric acid and stir to dissolve (the molar ratio of metal ions to citric acid is 1:1), then add ammonia water to adjust the pH to about 7, put it in an oil bath, adjust the temperature to 80℃ and keep it warm, and stir it continuously until a viscous gel is produced. Cover the surface of the gel with tin foil and heat it to 120℃ at a heating rate of 5℃ / min and keep it warm for 10h to remove excess water, then heat it to 200℃ at a heating rate of 5℃ / min and treat it at 200℃ for 2h to obtain the precursor, grind it thoroughly and transfer it to a corundum crucible, place it in a muffle furnace, and pre-sinter it at 450℃ for 3h at a heating rate of 5℃ / min, then heat it to 1300℃ at the same rate and keep it warm for 3h. Take out the sample after cooling, and grind it to obtain neodymium-doped W-type barium ferrite.

[0032] Neodymium-doped W-type barium ferrite, pyrrole and ferric chloride are added to an aramid fiber aqueous solution while stirring with a glass rod to obtain an aramid fiber solution reinforced with modified rare earth ferrite; the weight ratio of the modified rare earth ferrite, pyrrole, ferric chloride and aramid fiber aqueous solution is 8:5:5:72.

[0033] Step 2: Prepare modified rare earth ferrite reinforced aerogel.

[0034] The modified rare earth ferrite reinforced aramid fiber solution was placed in a silicone soft mold and frozen in a refrigerator with the temperature set at -20°C; the frozen sample was placed in a blast drying oven for drying with the temperature set at 100°C to obtain a modified rare earth ferrite reinforced aerogel.

[0035] Step 3: Prepare modified rare earth ferrite aerogel-based shielding-heat-conducting-anti-corrosion multifunctional composite materials.

[0036] The thermal conductive filler and the component A of the polydimethylsiloxane elastomer (component A is polydimethylsiloxane) are blended and stirred for 20 minutes, and then the component B of the polydimethylsiloxane elastomer (component B is a curing agent) is added, and the mixture is stirred for 20 minutes and placed in a vacuum oven for degassing to obtain a thermal conductive filler / polydimethylsiloxane elastomer. The thermal conductive filler has a density of 2.3 g / cm 3 of boron nitride and 3.3g / cm 3 The mass ratio of the thermal conductive filler, the component A of the polydimethylsiloxane elastomer, and the component B of the polydimethylsiloxane elastomer is 30:35:35.

[0037] The thermal conductive filler / polydimethylsiloxane elastomer was poured into a mold with a modified rare earth ferrite reinforced aerogel, and vacuum-assisted packaging was used. After packaging, it was placed in a forced air drying oven for curing at a temperature of 100°C to obtain a modified rare earth ferrite aerogel-based shielding-heat-conducting-anti-corrosion multifunctional composite material with a mesh structure. The mesh structure of the sample is as follows Figure 3 shown.

[0038] Example 2

[0039] This embodiment provides a modified rare earth ferrite aerogel-based shielding-heat-conducting-anti-corrosion multifunctional composite material, and its preparation method includes the following steps:

[0040] Step 1: Prepare a modified rare earth ferrite reinforced aramid fiber solution.

[0041] By weight, 20 parts of calcium chloride, 3 parts of p-phenylenediamine and 12 parts of terephthaloyl chloride are completely dissolved in 70 parts of nitrogen methyl pyrrolidone, the stirrer speed is adjusted to 400 rpm, and the reaction is carried out for 3 hours; 1000 ml of deionized water is added to the solution after the reaction, and a glass rod is used to stir while adding. The product is allowed to stand for a period of time to precipitate and then filtered. The viscous solution is wrapped with a filter to obtain a synthetic aramid fiber aqueous solution.

[0042] Neodymium-doped W-type barium ferrite was prepared by sol-gel method. The molecular formula of neodymium-doped W-type barium ferrite is Ba 1- x Nd x Co2Fe 16 O 27 , x is 0.15, and the preparation method is the same as that in Example 1.

[0043] Neodymium-doped W-type barium ferrite, pyrrole and ferric chloride are added to an aramid fiber aqueous solution while stirring with a glass rod to obtain a modified rare earth ferrite reinforced aramid fiber solution; the weight ratio of the modified rare earth ferrite, pyrrole, ferric chloride and aramid fiber aqueous solution is 5:4:4:92.

[0044] Step 2: Prepare modified rare earth ferrite reinforced aerogel.

[0045] The modified rare earth ferrite reinforced aramid fiber solution was placed in a silicone soft mold and frozen in a refrigerator with the temperature set at -20°C; the frozen sample was placed in a blast drying oven for drying with the temperature set at 80°C to obtain a modified rare earth ferrite reinforced aerogel.

[0046] Step 3: Prepare modified rare earth ferrite aerogel-based shielding-heat-conducting-anti-corrosion multifunctional composite materials.

[0047] The thermal conductive filler and the component A of the polydimethylsiloxane elastomer were blended and stirred for 20 minutes, and then the component B of the polydimethylsiloxane elastomer was added, and the mixture was stirred for 20 minutes and placed in a vacuum oven for degassing to obtain a thermal conductive filler / polydimethylsiloxane elastomer. The thermal conductive filler has a density of 4.0 g / cm 3 The mass ratio of the thermal conductive filler, the component A of the polydimethylsiloxane elastomer, and the component B of the polydimethylsiloxane elastomer is 30:35:35.

[0048] The thermal conductive filler / polydimethylsiloxane elastomer is poured into a mold containing modified rare earth ferrite reinforced aerogel, and vacuum assisted packaging is used. After packaging, it is placed in a forced air drying oven for curing at a temperature set to 80°C to obtain a modified rare earth ferrite aerogel-based shielding-thermal conductivity-anti-corrosion multifunctional composite material with a network structure.

[0049] Comparative Example 1

[0050] This comparative example provides a modified rare earth ferrite-reinforced aerogel, comprising step 1 and step 2 of embodiment 1.

[0051] Comparative Example 2

[0052] This comparative example provides a modified rare earth ferrite and a thermally conductive filler reinforced polydimethylsiloxane elastomer, the preparation method of which is as follows: directly blending neodymium-doped W-type barium ferrite powder (preparation method is the same as in Example 1) and a thermally conductive filler / polydimethylsiloxane elastomer (preparation method is the same as in Example 1) and curing them to obtain an aerogel without a network structure.

[0053] Performance Test:

[0054] The samples prepared in Example 1-2 and Comparative Example 1-2 were punched into rectangular blocks of 22.84 mm×10.12 mm×2 mm using a special mold, and the shielding performance, thermal conductivity and anti-corrosion performance were tested.

[0055] 1) Shielding effectiveness test: Use a vector network analyzer to test the shielding effectiveness of the sample in the range of 8-12.4GHz. The test results are shown in Figure 1 .like Figure 1 As shown, compared with comparative examples 1-2, the electromagnetic shielding performance of embodiments 1-2 is significantly enhanced.

[0056] 2) Anti-corrosion performance test: Place the sample in a salt spray chamber with a corrosion environment of 5% wt NaCl and 35°C for 7 days, and retest the shielding effectiveness of the sample. The electromagnetic shielding effectiveness test results of the sample after corrosion are shown in Figure 2 .like Figure 2As shown, the electromagnetic shielding performance of samples 1 to 2 of this embodiment does not decrease much before and after corrosion, can meet the electromagnetic shielding requirements, and has good anti-corrosion performance.

[0057] 3) Thermal conductivity test: The thermal conductivity of the samples was tested using a Hot Disk thermal conductivity tester. The test results of the thermal conductivity are shown in Table 1. As can be seen from Table 1, the samples of Examples 1 and 2 have good thermal conductivity.

[0058] Table 1 - Thermal conductivity test results

[0059]

[0060] The present invention provides a modified rare earth ferrite aerogel-based shielding-heat conduction-anti-corrosion multifunctional composite material with a mesh structure and a preparation method thereof. A conductive path is constructed by modifying rare earth reinforced aerogel to achieve excellent shielding effectiveness under corrosive conditions, and then a polydimethylsiloxane elastomer with excellent thermal conductivity is cast through structural design to improve the thermal conductivity and achieve shielding-heat conduction-anti-corrosion multifunctional integration. A flexible and lightweight high thermal conductivity structural electromagnetic shielding composite material is prepared by the preparation method described in the present invention. Through tests with a vector network analyzer and a thermal conductivity tester, it can be seen that compared with ordinary flexible electromagnetic shielding thermal conductive materials, the shielding effectiveness and thermal conductivity of the high thermal conductivity structural electromagnetic shielding composite material are greatly improved, proving the effective role of the structural design. In addition, it maintains excellent shielding effectiveness after long-term corrosive conditions, meeting the demand for durable use, and has important practical significance in the application of electromagnetic shielding materials in the future.

[0061] The above are only preferred embodiments of the present invention. The protection scope of the present invention is not limited to the above embodiments. All technical solutions under the concept of the present invention belong to the protection scope of the present invention. It should be pointed out that for ordinary technicians in this technical field, some improvements and modifications without departing from the principle of the present invention should be regarded as the protection scope of the present invention.

Claims

1. A method for preparing a modified rare earth ferrite aerogel-based shielding-heat-conducting-anti-corrosion multifunctional composite material, characterized in that: The following steps are involved: Step 1: Mixing and stirring the modified rare earth ferrite, pyrrole, ferric chloride and aramid fiber aqueous solution to obtain a modified rare earth ferrite reinforced aramid fiber solution; Step 2: freezing the modified rare earth ferrite reinforced aramid fiber solution, and drying the frozen sample to obtain a modified rare earth ferrite reinforced aerogel; Step 3: pour the thermal conductive filler / polydimethylsiloxane elastomer onto the modified rare earth ferrite reinforced aerogel, vacuum package it and then cure it to obtain a modified rare earth ferrite aerogel-based shielding-thermal conductive-anti-corrosion multifunctional composite material with a network structure.

2. The method for preparing the modified rare earth ferrite aerogel-based shielding-heat-conducting-anti-corrosion multifunctional composite material according to claim 1, characterized in that: In the step 1, the weight ratio of the modified rare earth ferrite, pyrrole, ferric chloride and aramid fiber aqueous solution is (4-8):(2-5):(2-5):(72-92).

3. The method for preparing the modified rare earth ferrite aerogel-based shielding-heat-conducting-anti-corrosion multifunctional composite material according to claim 1, characterized in that: In the step 1, the modified rare earth ferrite is neodymium-doped W-type barium ferrite, whose molecular formula is Ba 1-x Nd x Co2Fe 16 O 27 , x is 0.10, 0.15 or 0.20; The preparation method is: Will Ba 2+ 、Nd 3+ 、Co 2+ and Fe 3+ The salt is mixed with deionized water, citric acid is added and stirred to dissolve, and after the solution is adjusted to be neutral, the temperature is increased and stirred until a viscous gel is produced; the gel is further heated to remove excess water, and then the temperature is increased to 190-220° C. to obtain a precursor, and the precursor is ground; the ground precursor powder is calcined to obtain neodymium-doped W-type barium ferrite.

4. The method for preparing the modified rare earth ferrite aerogel-based shielding-heat-conducting-anti-corrosion multifunctional composite material according to claim 3, characterized in that: The molar ratio of citric acid to metal ions is 1:1; The calcination process is as follows: the ground precursor powder is placed in a muffle furnace, pre-calcined at 450° C. for 3 hours at a heating rate of 5° C. / min, and then heated to 1300° C. at a heating rate of 5° C. / min and kept at that temperature for 3 hours.

5. The method for preparing the modified rare earth ferrite aerogel-based shielding-heat-conducting-anti-corrosion multifunctional composite material according to claim 1, characterized in that: In the step 1, the method for preparing the aramid fiber aqueous solution is: Completely dissolving calcium chloride, p-phenylenediamine and terephthaloyl chloride in nitrogen methyl pyrrolidone, stirring at 150-400 rpm for 3-6 hours to react; adding water to the solution after the reaction and stirring, standing and filtering after the stirring, and using a filter to wrap the viscous solution to obtain a synthetic aramid fiber aqueous solution; The addition ratio of calcium chloride, p-phenylenediamine, terephthaloyl chloride, nitrogen methyl pyrrolidone and water is 20g: 3g:12g:70g:1000ml.

6. The method for preparing the modified rare earth ferrite aerogel-based shielding-heat-conducting-anti-corrosion multifunctional composite material according to claim 1, characterized in that: In the step 2, the freezing temperature is -20°C and the drying temperature is 60-100°C; In the step three, the curing method is: after the vacuum packaging is completed, it is placed in a forced air drying oven, and the temperature is set to 80-100° C. to obtain a cured modified rare earth ferrite aerogel-based shielding-heat-conducting-anti-corrosion multifunctional composite material.

7. The method for preparing the modified rare earth ferrite aerogel-based shielding-heat-conducting-anti-corrosion multifunctional composite material according to claim 1, characterized in that: In the step 3, the preparation method of the thermal conductive filler / polydimethylsiloxane elastomer is: The thermal conductive filler and component A of the polydimethylsiloxane elastomer are blended and stirred once, and then component B of the polydimethylsiloxane elastomer is added, and the mixture is stirred for a second time and placed in a vacuum oven for degassing to obtain a thermal conductive filler / polydimethylsiloxane elastomer.

8. The method for preparing the modified rare earth ferrite aerogel-based shielding-heat-conducting-anti-corrosion multifunctional composite material according to claim 7, characterized in that: The mass ratio of the thermal conductive filler, the component A of the polydimethylsiloxane elastomer and the component B of the polydimethylsiloxane elastomer is (20-30): (35-40): (35-40); The first stirring time is 20 min, and the second stirring time is 20 min.

9. The method for preparing the modified rare earth ferrite aerogel-based shielding-heat-conducting-anti-corrosion multifunctional composite material according to claim 7, characterized in that: The thermally conductive filler has a density of 2.3 g / cm 3 Boron nitride, 3.3g / cm 3 Aluminum nitride, 3.2g / cm 3 Silicon carbide and 4.0g / cm 3 At least one of aluminum oxides.

10. A modified rare earth ferrite aerogel-based shielding-heat-conducting-anti-corrosion multifunctional composite material, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Rare-earth-based aerogel material with radiation shielding effect and heat insulation property as well as preparation and application of rare-earth-based aerogel material

    CN110563435A

  • Graphene oxide aerogel-based electromagnetic shielding polymer composite material with electric conduction-thermal conduction dual-network structure and preparation method thereof

    CN112876848A

  • Aramid nanofiber and carbonyl iron powder composite aerogel as well as preparation method and application thereof

    CN116655997A

  • Methods for the manufacture of thermal interfaces, thermal interfaces, and articles comprising the same

    US20180249593A1